2014
DOI: 10.1038/ejhg.2014.211
|View full text |Cite
|
Sign up to set email alerts
|

Compound heterozygous or homozygous truncating MYBPC3 mutations cause lethal cardiomyopathy with features of noncompaction and septal defects

Abstract: Familial hypertrophic cardiomyopathy (HCM) is usually caused by autosomal dominant pathogenic mutations in genes encoding sarcomeric or sarcomere-associated cardiac muscle proteins. The disease mainly affects adults, although young children with severe HCM have also been reported. We describe four unrelated neonates with lethal cardiomyopathy, and performed molecular studies to identify the genetic defect. We also present a literature overview of reported patients with compound heterozygous or homozygous patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 43 publications
(53 reference statements)
4
52
1
Order By: Relevance
“…30 Mechanisms responsible for this apparent phenotypic overlap with other cardiomyopathies are incompletely understood.…”
Section: Compound/homozygote Radical Mybpc3 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Mechanisms responsible for this apparent phenotypic overlap with other cardiomyopathies are incompletely understood.…”
Section: Compound/homozygote Radical Mybpc3 Mutationsmentioning
confidence: 99%
“…Of note, in both animal models 56,57 and some of the case reports with double radical MYBPC3 mutations, [29][30][31] severe systolic dysfunction and ventricular dilatation were described as were signs of noncompaction. 30 Mechanisms responsible for this apparent phenotypic overlap with other cardiomyopathies are incompletely understood.…”
Section: Compound/homozygote Radical Mybpc3 Mutationsmentioning
confidence: 99%
“…The remaining cardiac gene variants represent a subset associated with factors such as digenic inheritance, low penetrance, population specific variation, or potential role as disease modifiers, causing their classification to be conservative, even with significant occurrences of the variant in the control population. 16,17 Nine of the 12 (75%) Lynch syndrome variants with an ExAC frequency exceeding the MPAF were in the PMS2 gene. Analysis of variants in PMS2 is challenging owing to the presence of numerous pseudogenes with high homology that preclude unequivocal differentiation between true variants versus those originating in the pseudogenes.…”
Section: Discussionmentioning
confidence: 99%
“…5 In this study, a significantly poor outcome was observed in a minority of young NCCM and DCM patients, partly explained by homozygous and compound heterozygous mutations. 39 Because MYBPC3 founder mutations are truncating mutations leading to haploinsufficiency, 8 compound heterozygous or homozygous mutations would theoretically result in human MYBPC3 knockouts (no functional MYBPC3 protein), leading to severe HF at a young age. 39 The likelihood of compound heterozygotes or homozygotes in countries with founder mutations is increased.…”
Section: Nccm and Dcm In Fg+ Carriersmentioning
confidence: 99%
“…39 Because MYBPC3 founder mutations are truncating mutations leading to haploinsufficiency, 8 compound heterozygous or homozygous mutations would theoretically result in human MYBPC3 knockouts (no functional MYBPC3 protein), leading to severe HF at a young age. 39 The likelihood of compound heterozygotes or homozygotes in countries with founder mutations is increased. 5 The finding of NCCM and DCM in the FG+ population and within 1 family supports previous suggestions that the various cardiomyopathies are part of a cardiomyopathy spectrum with similar pathogenesis.…”
Section: Nccm and Dcm In Fg+ Carriersmentioning
confidence: 99%